2018
DOI: 10.3917/mouv.093.0127
|View full text |Cite
|
Sign up to set email alerts
|

Soutien politique et soutien humanitaire. Retour sur les solidarités citoyennes avec les réfugié·e·s en Belgique

Abstract: Focalisé sur le cas de la Belgique, cet article analyse la manière dont l’espace militant du soutien aux migrant·e·s est structuré autour d’une dyade séparant le « politique » de « l’humanitaire ». Cette opposition serait légitimée par les divergences entre les répertoires d’actions, selon qu’ils visent à la transformation radicale de la politique migratoire ou qu’ils soient centrés sur l’aide à la personne. L’article nous apprend que ces catégories sont en réalité poreuses et dépendent bien souvent du context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Among our case studies, we observed actions contextually motivated by humanitarian concerns, by criticism specifically targeting the institutional system of reception as well as migration politics more broadly -and their effect in producing "illegal" migrants (De Genova 2002) -and by the will to promote a more inclusive form of citizenship. These three frames of action often overlapped in most of the sites where we conducted research, becoming porous categories (Vertongen 2018). Moreover, they interact with other factors (namely network dynamics) and additional rationales that we will illustrate in the following sections.…”
Section: Pro-migrant Mobilization Actions -Frames Of Mobilizationmentioning
confidence: 98%
“…Among our case studies, we observed actions contextually motivated by humanitarian concerns, by criticism specifically targeting the institutional system of reception as well as migration politics more broadly -and their effect in producing "illegal" migrants (De Genova 2002) -and by the will to promote a more inclusive form of citizenship. These three frames of action often overlapped in most of the sites where we conducted research, becoming porous categories (Vertongen 2018). Moreover, they interact with other factors (namely network dynamics) and additional rationales that we will illustrate in the following sections.…”
Section: Pro-migrant Mobilization Actions -Frames Of Mobilizationmentioning
confidence: 98%
“…My 'non-presence' during 2015 provided a certain (emotional) distance to the subject under study and I first came to know Maximilian Park through narra- De Praetere, 2016;Vertongen, 2018). Additionally, in 2017 and 2019, insights were gained through participatory and non-participatory observation in the park and with the Platform.…”
Section: Maximilian Park: From Site Of 'Crisis' To An Established Space Of Arrivalmentioning
confidence: 99%
“…While encounters with the "other" might lead to reflecting on one's own favorable circumstances and privileges, it often fails to challenge the mechanisms, structures, and institutions that produce and stabilize exclusion and oppression and thereby generate disparities (Wilson, 2017). Following these considerations, there has been a recent debate (especially since 2015) on the disruptive and transformative potential of migrant and refugee support and whether it is politicizing and subversive or merely reproducing the status quo through a humanitarian approach (see Rygiel, 2011Rygiel, , 2012van Dyk and Misbach, 2016;Fleischmann and Steinhilper, 2017;Frykman and Mäkelä, 2019; specifically for the case of Plateforme Citoyenne and migrant support in Brussels, see Depraetere and Oosterlynck, 2017;Vertongen, 2018;Lafaut and Coene, 2019;Vandervoordt, 2019;Saltiel, 2020). So far, this discussion, too, is entirely based on public discourse.…”
Section: Introductionmentioning
confidence: 99%